(3GdJQHjI hGdJYdje aj GdESdGes - (3eWgQj, eQJVis ((3HjQhJs (3OGQ GdgGOjs, 2009)
(3Ef GdeJhLH aj GdJQHjI hGdJYdje gh HfGA TNUjI GdEfSGf(B. (3aGdYbjOI GdJj gj PGJ GdCgOGa GdeMOOI hGdebQQGJ GdTGedI hGdJj dgG HMSH GdeUWdM fXGe bVGFj hGbJUGOj hCSGSj dG jecf Cf dG jchf dgG fXGe JQHhj NGU, Cj Cf GdYbjOI GdJj JQjO JWHjb eNWWGJ CNdGbjI hSjGSjI hGbJUGOjI NGUI Hjf GdfGS, gj HGdJGdj JQjOgG ddfGS, Cge ef Cf jchf GdgOa gh GdaQO Ch GdeLJeY, hgPG aj MO PGJg CeQ jSdW Ydjg GdeDda GdCVhGA aj HMKg aj gPG GdcJGH(B. (3aEf cGf GdgOa gh GdeLJeY adG HO aj fgGjI GdCeQ ef GdGYJeGO Ydi gDdGA GdaQGO aj JWHjb gPg GdNWW, hdG HO ef JQHjJge hJYdjege HTcd jJecfhf efg ef JWHjb gPg GdNWW aj GdeLJeY, hEf cGf GdgOa gh GdaQO, aMjfFP jchf ef GdHOjgj JYdje GdCaQGO hJQHjJge, haj GdESdGe JMaX CUGdI GdaQO hGdeLJeY, adG HO ef hLhO eNWW hHQfGeL dHfGA GdaQO HhVYg ebOeI dHfGA GdeLJeY hGdCeI(B. (3aHfGA TNUjI GdaQO VQhQj ef LgI Cf GdaQO faSg gOa ddJQHjI, hef LgI chfg ebOeI dHfGA GdeLJeY GdUGdM(B. (3ef gPG GdefWdb cGf dG HO ef GdJYQa Ydi CUhd GdJQHjI hGdJYdje aj GdESdGe(B. (3hef gfG LGA gPG GdHMK GdPj jMGhd GdeDda ef NdGd EOGA gPg GdegeI eHfjkG aEPG cGf GdESdGe jYjQ GgJeGekG dCeQ GdJYdje ef CLd GdJQHjI hGdfhYjI Ce dG, hHYHGQI CNQi(B: (3gd Cf GdESdGe jYJfj HJfejI Ybd hacQ GdEfSGf Ce djS dg gPg GdYfGjI(B. (3hgPg gj faS eSCdI GdYde GdJj cGfJ eWQhMI Hjf GdYdeGA efP GdbOe(B. (3aCSGS GdeWdH gd Cf GdESdGe OYG Ydi GdYde? heG gj NUhUjGJ GdYde GdPj OYG Zdjg GdESdGe? MjK HMK Pdc YdeGA ef fXjQ GdZRGdj hGdajV hBNQhf(B. (3hef fGMjI CNQi, aEf hLgI GdfXQ GdJQHhjI hGdJYdjejI aZf ebQQGJ GdESdGe GdCNdGbjI JgOa dJQHjI GdEfSGf GdPj jQjOg GdESdGe, aef gh GdEfSGf? GdeSde GdfehPLj? heG gj NUGFUg? hef fGMjI KGfjI gfGdc eSGFd CNQi JQJHW HcjajI JWHjb GdCgOGa? Cj Cf GdgOa hGVM, hcd eG gh GdTcd hGdWQjb GdPj jfHZj Sdhcg ef CLd JQHjI GdEfSGf? hEdi Cj eOi dhMXJ GdbVGjG GdfaSjI aj GdESdGe? eKdkG aj JYdje GdWad hJQHjJg, eG gj GdJhLjgGJ GdESdGejI? hEdi Cj MqO QhYj GdhGbY hGdbVGjG GdfaSjI aj Jdc GdJhLjgGJ? hHGdfSHI deG eVi, eG gh ebOGQ GfWHGb JQHjJfG hJYdjefG GdSGHb eY GdJYGdje GdESdGejI? heG gh ebOGQ YOe GfWHGbgG? heG gh eOi JWHjb GdJQHjI hGdJYdje aj YUQfG?(B. (3gPG eG MGhd GdeDda GdELGHI Ydjg aj HMKg gPG Vef EWGQ ehVhYj hefgL Ydej hQDjI JMdjdjI hGYjI dbVGjG GdJQHjI hGdJYdje aj GdeLJeY GdESdGej(B.s
(3GdfhY (B: (3cJGHs
Keywords: Education Islamique; Islamic Education; (3GdJQHjI GdGSdGejIs